2003
DOI: 10.1124/jpet.103.054908
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Spontaneous and Precipitated Nicotine Withdrawal in the Mouse

Abstract: The nicotine withdrawal syndrome was validated and characterized in the mouse using both somatic and affective measures after infusion with nicotine daily via subcutaneous minipumps. The influence of dose, duration of infusion, and repeated withdrawal as well as the contribution of genetic factors were investigated. We then characterized the contribution of nicotinic receptor and site mechanisms to withdrawal signs using various nicotinic antagonists. Our results showed that spontaneous nicotine withdrawal inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
252
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(281 citation statements)
references
References 20 publications
20
252
4
1
Order By: Relevance
“…This result supports previous research that has shown that somatic nicotine withdrawal symptoms are not present in mice that are withdrawn from 6 mg/kg/day nicotine (Damaj, Kao, & Martin, 2003).…”
Section: The Effects Of Dhβe-precipitated Withdrawal Are Not Due To Ssupporting
confidence: 92%
See 1 more Smart Citation
“…This result supports previous research that has shown that somatic nicotine withdrawal symptoms are not present in mice that are withdrawn from 6 mg/kg/day nicotine (Damaj, Kao, & Martin, 2003).…”
Section: The Effects Of Dhβe-precipitated Withdrawal Are Not Due To Ssupporting
confidence: 92%
“…For instance, DHβE-precipitated withdrawal produced limited somatic signs of nicotine withdrawal with higher doses of nicotine (Damaj et al, 2003). However, DHβE antagonizes both β2 and β4-containing nAChRs (Harvey et al, 1996;Williams & Robinson, 1984) so it is unclear if the DHβE-precipitated somatic withdrawal symptoms were associated with β2 or β4-containing nAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…increased grooming, scratching, or shaking) in rats or mice that occur following spontaneous withdrawal or nAChR antagonist-precipitated withdrawal [28,77,103,102]. Additionally, mice withdrawn from chronic nicotine have been evaluated using the elevated plus maze, in which the percentage of time spent on the open arms of the maze serves as a measure of anxiety [28,77]. Mice withdrawn from nicotine spend less time on the open arms relative to saline controls, indicating increased anxiety [28,77].…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
“…Additionally, mice withdrawn from chronic nicotine have been evaluated using the elevated plus maze, in which the percentage of time spent on the open arms of the maze serves as a measure of anxiety [28,77]. Mice withdrawn from nicotine spend less time on the open arms relative to saline controls, indicating increased anxiety [28,77]. Furthermore, nicotine withdrawal-related deficits in contextual learning have been evaluated in mice [33,30,132,133].…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
“…Other studies indicate that rats receiving chronic infusion of nicotine (6 mg/kg/day) over a 28-day period exhibit analgesia with development of tolerance, in some pain tests (Carstens et al, 2001;Zbuzek and Chin, 1994). Noteworthy is the fact that spontaneous or precipitated withdrawal from chronic nicotine administration (24 mg/kg/day for 14 days) produced hyperalgesia in mice (Damaj et al, 2003). Kishioka et al (2006) measured serum corticosterone levels in ICR mice as an index of "cross-talk" between nicotine and the opioid system.…”
Section: Animal Studiesmentioning
confidence: 99%